Penyuluhan dan Pemeriksaan Kesehatan Gigi dan Mulut pada Komunitas Mutiara Senja - Gereja Santo Andreas - Louisa, Marie; Damayanti Marpaung, Carolina; Leny Raiyon, Maria; Tjandrawinata, Rosalina; Juslily, Marta (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Oral health can affect general health and quality of life; therefore it is very important for the elderly to understand the importance of oral health. Physical decline in the elderly can be seen through sagging skin, hair discoloration, and loss of vision and teeth. This condition can be exacerbated by poor oral hygiene. Based on previous research, it has been found that of the 71% of elderly who brush their teeth every day, only 2.9% brush their teeth at the right time. Therefore, the counseling activity was carried out on Saturday, May 17, 2025 at the Mutiara Senja Elderly Community, Santo Andreas Church. The method used in the counseling was the lecture method and providing education through PowerPoint media. Evaluation of participant knowledge was carried out before and after the counseling by providing multiple-choice assessment sheets to determine the level of knowledge. Based on the evaluation results, it was found that there was an increase in the level of knowledge of the counseling participants. This can be seen in the average post-test score which increased compared to the pre-test score